A HR-XPS study of the formation of h-BN on Ni(111) from the two precursors, ammonia borane and borazine - Bachmann, Philipp; Düll, Fabian; Späth, Florian; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2018)
Together with borazine, ammonia borane is a prominent precursor molecule for the formation of hexagonal boron nitride, which is of high interest as a 2D-material and graphene analog. Ammonia borane is also a possible solid hydrogen carrier for renewable energies with high storage density. Using X-ray photoelectron spectroscopy and temperature-programmed desorption, we investigated low-temperature adsorption and dehydrogenation during heating of borazine and ammonia borane on Ni(111) to form h-BN. For borazine, we observe the formation of disordered boron nitride above 300 K, which starts to form hexagonal boron nitride above 600 K. Ammonia borane shows multiple dehydrogenation steps at the boron and nitrogen atoms up to 300 K. This results in various BHxNHy species, including borazine-like intermediates, before the formation of disordered boron nitride and finally hexagonal boron nitride, analogous to the borazine decomposition. Published by AIP Publishing.